2022
DOI: 10.1063/5.0085796
|View full text |Cite
|
Sign up to set email alerts
|

Study on the radial sectional velocity distribution and wall shear stress associated with carotid artery stenosis

Abstract: Atherosclerosis is an important cause of cardiovascular disease. The wall shear stress (WSS) is one of the key factors of plaque formation and dislodgement. Currently, WSS estimation is based on the measurement of the blood velocity gradient. However, due to the lack of flow field measurements in carotid stenosis vessels, the two distribution forms (parabolic and non-parabolic) commonly considered in numerical simulations could cause WSS estimates to differ by more than 40%, which could seriously affect the ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…More recently, Song et al (2022) [ 71 ] created an experimental model of real-structure carotid arteries with stenosis caused by atherosclerotic plaques, applying 3D printing technology. This work aimed to obtain a 3D printed model based on real configuration data to simulate the stenotic blood flow caused by carotid plaques.…”
Section: Additive Manufacturing To Reproduce Atherosclerotic Blood Ve...mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Song et al (2022) [ 71 ] created an experimental model of real-structure carotid arteries with stenosis caused by atherosclerotic plaques, applying 3D printing technology. This work aimed to obtain a 3D printed model based on real configuration data to simulate the stenotic blood flow caused by carotid plaques.…”
Section: Additive Manufacturing To Reproduce Atherosclerotic Blood Ve...mentioning
confidence: 99%
“…The 3D printed model had a layer thickness of 0.1 mm and was achieved by the SLA technique using a transparent photosensitive resin. The authors concluded that 3D printed models could support the understanding of carotid artery stenosis flow characteristics accurately, and that numerical simulation was a reliable method for studying the blood flow under stenotic conditions [ 71 ].…”
Section: Additive Manufacturing To Reproduce Atherosclerotic Blood Ve...mentioning
confidence: 99%
“…Patient-specific imaging data obtained from CT or MRI scans can be used to print a 3D phantom of the diseased vessel. Various groups used this approach to mimic stenosed coronary or carotid arteries and used them to validate their computational fluid dynamic models [155,156].…”
Section: Tissue-engineered Models For Advanced Atherosclerosismentioning
confidence: 99%